Psychometric analysis of the short-form UCLA Loneliness Scale (ULS-6) in older adults - Felix Neto (2014)
The aim of this investigation was to present new empirical evidence regarding the psychometric properties of the short-form UCLA Loneliness Scale (ULS-6) among Portuguese older people. The study included 1,154 persons (60 % women and 40 % men), aged 60-90 (M = 71.26; SD = 6.66). The psychometric properties of the ULS-6 were analysed by means of confirmatory factor analysis, internal consistency, and criterion-related validity methods. Confirmatory factor analysis supported a unidimensional structure of the measure with adequate values of various fit indices. The ULS-6 presented satisfactory psychometric properties, with a high level of internal consistency. Furthermore, the ULS-6 showed a negative relationship with self-esteem, satisfaction with life, and positive affect; and a positive one with negative affect. The results confirm that the ULS-6 provides a brief, psychometrically sound measure of loneliness that is appropriate for use among older adults.